Proceedings of the International Conference on Business and Management Dynamics 2016 Sustainable economies in the information economy - Twum-Darko, Michael (AOSIS, 2016)
Cape Town, South Africa, 7 Sept. 2016 - 8 Sept. 2016. Theme: Sustainable economies in the information economy. Purpose: To share the quality academic papers presented at the International Conference on Business and Management Dynamics (ICBMD) held from 7 to 8 September 2016 at African Pride Crystal Hotel and Spa in Cape Town. As grey literature, the proceedings are the contributions made by researchers at the conference and are considered the written record of the work that was presented to fellow conference delegates. Methodology: The methodology used varies from researcher to researcher but are suitable for the studies conducted. Thus, on the one hand, studies that were subjective in nature used the interpretive paradigm, where the qualitative approach adopted made used of the interview method to collect data. On the other hand, studies that were objectively inclined adopted the positivist philosophy and used survey questionnaires to collect data. However, there were some academic papers which used mixed methodology because of the nature of the study. Whatever methodology used adhered to the ethos of the philosophies underpinning the methodology. Contribution made to scholarship: The articles come from individual researchers and each article in the proceedings is unique. Mostly, there is no general argument leading from one contribution to the next. However, it is interesting to note that in the area of economic performance it was evident that real exchange rate and net foreign direct investment contribute more towards innovations in economic growth. With regard to human capital development, papers presented evidence that there exists a definite need to explore the phenomenon of personal branding as limited scientific academic research has been done within the field of personal branding or on elements of the topic. Thus, the outcome argues that personal branding has an influence on leadership style which in turn impacts on organisational performance and related hygiene factors. Furthermore, it was demonstrated that current methods or strategies for enforcing institutionalisation of knowledge sharing within an organisation have not been successful, and, as such, new strategies are needed to reinforce efforts to nurture and invigorate the institutionalisation of knowledge sharing within an organisation. With regard to technology and big data impact on organisational performance, it was evident that system performance, memory consumption and CPU utilisation can be used as criteria to compare and evaluate big data technologies to improve organisational performance. Most of the articles' contribution reemphasised technology education and training as a means of digitising business and improving effectiveness. Target audience: The target readership is academic researchers and business leaders who require access to the latest developments in the fields of economics, information management, business, education, development studies, social sciences and technology. It is also for policymakers and other stakeholders who need a better understanding of the impact of new developments on existing policies and regulations for their review or amendment.